Orienting safety assurance with outcomes of hazard analysis and risk assessment: A review of the ISO 15066 standard for collaborative robot systems. (September 2020) - Chemweno, Peter; Pintelon, Liliane; Decre, Wilm
Highlights: We review safety assurance methods for collaborative robot systems described in ISO 15066. We evaluate orientation of design safeguards to hazard analysis and risk assessment. We propose a framework for aligning design safeguards to risk assessment. Abstract: Close interactions with a human operator are an important safety concern for collaborative robot systems. For safety assurance, robot integrators are required to demonstrate that they have taken steps to identify potential hazards, which may be embedded in collaborative tasks, or embedded within the collaborative workspace. Consequently, design safeguards are developed to mitigate unintended contact, which may be hazardous to the human co-worker, while performing cooperative or collaborative tasks. The ISO 15066 standard proposes guidelines, which designers, integrators, and users need to consider when embedding passive and active safeguards on the robot system, or while designing collaborative workspaces. Importantly, the standard premises such safeguards on structured hazard analysis and risk assessment processes. However, from studies in literature, it is often unclear how designers, integrators or users can orient design safeguards to outcomes of hazard analysis and risk assessment. Often it is unclear which steps designers need to follow, or which methods they can use to analyze hazards and assess risks, which may occur when robot systems and human co-worker perform collaborative/cooperative manufacturing tasks. Consequently, verifying the sufficiency of design safeguards to mitigate hazardous interactions in a manufacturing cell is challenging. This article reviews requirements for safety assurance of collaborative robot systems discussed in the recent ISO 15066 standard for collaborative robots and how such safeguards are realized in studies discussed in literature. The review explores gaps and propose a framework based on the ISO 31000 for orienting design safeguards for collaborative robots to outcomes of hazard analysis and risk assessment.